A visual fluoresce covalent organic polymer for precise analysis of Fe3+ in MC3T3-E1 cells: A method for bone disease diagnosis - Wenqiang Li (Elsevier, 2021)
Precise detection of Fe3+ ions in vitro is important for diagnosis of disease and bone health. Covalent organic polymers (COPs) are chosen as the precision probes, due to their light-weight, stable-bonds, and fast-response. In this work, a new fluorescent COP, pyrene-2,7-diboronic-COP(PD-COP), was designed and its feasibility in detection of iron concentration in cells was tested. PD-COP showed good performance in selective detection of Fe3+, among other metal ions. Its high anti-interference property and recyclability provide the theoretical basis for practical applications. PD-COP could selectively detect Fe3+ ions with low limit of detection (LOD) at a concentration of about 0.68 µM. The quenching mechanism could be due to the transfer of electron. The in vitro experiments using cells also showed that the PD-COP had good biocompatibility, and the ability to detect Fe3+ ions in cells. In conclusion, we successfully synthesized a novel COP, with high sensitivity that could selectively detect Fe3+ ions. The COP had the ability to enter the cell membrane and combine with iron ions, which provided a new method of monitoring bone health.